2005
DOI: 10.1002/jmv.20497
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sapovirus infection among Japanese infants in a day care center

Abstract: A total of 921 fecal specimens collected from 44 infants in a day care center in Tokyo, Japan during June 1999 to July 2000 were tested for the presence of sapovirus by reverse transcription-polymerase chain reaction (RT-PCR). Of 88 fecal specimens from infants with acute gastroenteritis, 2.3% (2) were found to be positive for sapovirus. Twenty-two of 833 (2.6%) fecal specimens collected from asymptomatic infants were also infected with this virus. Another interesting feature was the demonstration of high inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 26 publications
4
28
0
Order By: Relevance
“…Subclinical (asymptomatic) sapovirus infection was also detected (4,6,21,134,135,(213)(214)(215)(216). Quantitative PCR analysis revealed that asymptomatic individuals also shed sapovirus in the feces at levels comparable to those shed by individuals with gastroenteritis (182,183).…”
Section: Symptoms and Severity Of Diseasementioning
confidence: 94%
“…Subclinical (asymptomatic) sapovirus infection was also detected (4,6,21,134,135,(213)(214)(215)(216). Quantitative PCR analysis revealed that asymptomatic individuals also shed sapovirus in the feces at levels comparable to those shed by individuals with gastroenteritis (182,183).…”
Section: Symptoms and Severity Of Diseasementioning
confidence: 94%
“…Noroviruses are a major cause of both sporadic cases and outbreaks of gastroenteritis [4][5][6][7] whereas sapoviruses have been detected in many areas in the word but only infrequently, a few outbreaks of sapovirus have been reported [8][9][10][11][12] and the impact of the sapoviruses has not been fully established. Sapoviruses were primarily associated with cases of pediatric acute gastroenteritis [13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 98%
“…There have been reports of sapovirus outbreaks involving children [Akihara et al, 2005;Phan et al, 2006] and adults [Johansson et al, 2005;Yan et al, 2005] all over the world. Adenovirus and astrovirus has been detected in patients with diarrhea in many countries, including China (2% and 8%, respectively) [Liu et al, 2006], Botswana (2.8% and 2.7%) [Basu et al, 2003], Tunisia (6% and 7%) [Fodha et al, 2006], Argentina (3% and 7.6%) [Giordano et al, 2001;Bereciartu et al, 2002], Italy (6% and 7%) [Galdiero et al, 2005;Colomba et al, 2006], and United Kingdom (7.9% and 2.3%) [Simpson et al, 2003].…”
Section: Introductionmentioning
confidence: 98%